2019
DOI: 10.13102/sociobiology.v66i3.4266
|View full text |Cite
|
Sign up to set email alerts
|

Emerging vistas of Remote Sensing Tools in Pollination Studies

Abstract: With the growth of information and technology across the globe, remote sensing applications find a place in the ecological studies of pollinators. The utilization of remote sensing tools in understanding the ecosystem services rendered by the bee pollinators is reviewed here. We discussed how radar and radio telemetry techniques helps to track individual bees, their foraging behaviour and density in relation to altered phenology of flowering crops in a landscape. Role of satellite imagery tools in studying cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Recent works continue to fill research gaps in equipment [ 96 , 97 , 98 ], reflectivity, and insects’ geometrical characteristics [ 99 , 100 , 101 , 102 ]. As shown earlier, radar applications focus on either biodiversity/conservation [ 103 , 104 , 105 , 106 , 107 ] or agriculture (economically important insects [ 108 , 109 , 110 ] and pest management [ 21 , 111 , 112 , 113 , 114 , 115 , 116 ]).…”
Section: Insect Radarmentioning
confidence: 99%
“…Recent works continue to fill research gaps in equipment [ 96 , 97 , 98 ], reflectivity, and insects’ geometrical characteristics [ 99 , 100 , 101 , 102 ]. As shown earlier, radar applications focus on either biodiversity/conservation [ 103 , 104 , 105 , 106 , 107 ] or agriculture (economically important insects [ 108 , 109 , 110 ] and pest management [ 21 , 111 , 112 , 113 , 114 , 115 , 116 ]).…”
Section: Insect Radarmentioning
confidence: 99%
“…For example, tree density could be used to estimate the nesting suitability of pollinators like mason bees ( Osmia spp.) (Krishnasamy et al, 2019), which favor woody substrates for nesting.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, these advantages have been almost exclusively used in pollination studies to assess habitat composition in set perimeters (Willcox et al, 2018). However, RSD have the potential to contribute further to the study of pollinators, for example, by enabling the analysis of spatiotemporal landscape changes affecting pollinators or by assisting the mapping of floral (e.g., flower phenology and abundance) and nesting (e.g., tree density or soil physiographic factors) resources (Krishnasamy et al, 2019). These contributions represent a novel opportunity to improve our understanding of pollinators and their delivery of pollination services (Willcox et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…capturing changes in the spectral signatures or structural traits of vegetation (at different grains, depending on the sensor and platform used) so that their physiological, biochemical and spatial properties can be analyzed. When using remote sensing to characterize flowering vegetation, researchers have obtained can information in the form of multispectral images, reflectance spectra, or point cloud data (Willcox et al, 2018;Krishnasamy et al, 2019). Traditional field techniques involving manual floral counts using quadrats or transects are often laborious, time-consuming and only measure floral features detectable or predefined by the observers' eyes Furthermore, in an analysis of methodologies employed by 159 studies, Szigeti et al (2016) found that ecologists use a wide range of manual sampling methods but those are often not reported in sufficient detail, leading to a lack of standardization of sampling methods within the field.…”
Section: Spatial Resolution (M)mentioning
confidence: 99%
“…Important platforms for use in field studies are consumergrade fixed-wing and rotor-based drones (take-off weight totals less than 30 kg; Anderson and Gaston, 2013;Krishnasamy et al, 2019;Rominger et al, 2021). They are typically also equipped with GPS so that the captured images can be georeferenced.…”
Section: Structure From Motion (Sfm) Photogrammetrymentioning
confidence: 99%